KARY A AL TERNATIF MAHASISWA (KAM) PENGEMBANGAN KEWIRAUSAHAAN PERCETAKAN SABLON MAHASISW A JURUSAN PLB FIP UNIVERSITAS NEGERI YOGYAKARTA - -, Haryanto (Universitas Negeri Yogyakarta, 2003)
This program is aimed at givmg the students knowledge and practical skills through screen printing training in skill education subject in special education department. The objectives 6:f'the